Grateful American : a journey from self to service - Sinise, Gary (Nelson Books, 2019)
Gary Sinise shares the never-before-told story of his journey from trouble-making Chicago kid to cofounder of the legendary Steppenwolf Theater Company, world-famous actor, and tireless advocate for America's active duty defenders, veterans, and first responders.